Service Quality in Tourism Public Health: Trust, Satisfaction, and Loyalty - Han, Jiayu; Zuo, Yifan; Law, Rob; Chen, Sirong; Zhang, Mu (Frontiers in Psychology, 2021)
The spread of COVID-19 and large-scale travel restrictions have caused serious damage to the global tourism industry. Tourists pay additional attention to public health services and their health during travel, but studies on tourism public health service quality (TPHSQ) are limited. Therefore, this study aims to define TPHSQ and revise and validate its scale. The result of exploratory factor analysis indicates that TPHSQ includes two dimensions “overall environmental image” and “public health facilities and management”. And based on 456 valid samples, the relationship among TPHSQ, tourists’ trust, satisfaction, and loyalty was validated using the multiple linear regression model. Results revealed the importance of the TPHSQ in improving tourists’ satisfaction and recovering their trust and loyalty. These results provided several implications for research, practice, and society that can benefit diverse stakeholders, which could accelerate the recovery of the tourism industry.